Nutrition therapy for critically ill patients across the Asia–Pacific and Middle East regions: A consensus statement. (April 2018) - Sioson, Marianna S.; Martindale, Robert; Abayadeera, Anuja; Abouchaleh, Nabil; Aditianingsih, Dita; Bhurayanontachai, Rungsun; Chiou, Wei-Chin; Higashibeppu, Naoki; Mat Nor, Mohd Basri; Osland, Emma; Palo, Jose Emmanuel; Ramakrishnan, Nagarajan; et al.
Summary: Background & aims: Guidance on managing the nutritional requirements of critically ill patients in the intensive care unit (ICU) has been issued by several international bodies. While these guidelines are consulted in ICUs across the Asia–Pacific and Middle East regions, there is little guidance available that is tailored to the unique healthcare environments and demographics across these regions. Furthermore, the lack of consistent data from randomized controlled clinical trials, reliance on expert consensus, and differing recommendations in international guidelines necessitate further expert guidance on regional best practice when providing nutrition therapy for critically ill patients in ICUs in Asia–Pacific and the Middle East. Methods: The Asia–Pacific and Middle East Working Group on Nutrition in the ICU has identified major areas of uncertainty in clinical practice for healthcare professionals providing nutrition therapy in Asia–Pacific and the Middle East and developed a series of consensus statements to guide nutrition therapy in the ICU in these regions. Results: Accordingly, consensus statements have been provided on nutrition risk assessment and parenteral and enteral feeding strategies in the ICU, monitoring adequacy of, and tolerance to, nutrition in the ICU and institutional processes for nutrition therapy in the ICU. Furthermore, the Working Group has noted areas requiring additional research, including the most appropriate use of hypocaloric feeding in the ICU. Conclusions: The objective of the Working Group in formulating these statements is to guide healthcare professionals in practicing appropriate clinical nutrition in the ICU, with a focus on improving quality of care, which will translate into improved patient outcomes.